Conceptual solution for enhancing the electrolyser power supply system and hydrogen production - Kovačević, Nikola; Lazović, Kristina; Igić, Milorad; Dobričić, Sava (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
The paper presents a realized solution for powering an alkaline electrolyser for hydrogen production and offers a proposal for its improvement. By connecting photovoltaic panels, via a DC-DC converter, directly to the DC side of the existing twelve-pulse rectifier, it is possible to achieve savings in electrical energy necessary for hydrogen production through the alkaline electrolysis process. Measurements of electrical quantities for the existing power supply system are provided, along with a simulation of the improved system’s operation and a proposal for its more efficient control. Hydrogen obtained using energy from renewable sources in the electrolysis process is green hydrogen, which will be a significant energy carrier in the future and the backbone of the energy transition.